Anti-Gastric Cancer Activity of the Cell-free Culture Supernatant of Serofluid Dish and Lactiplantibacillus plantarum YT013 - Zhang, Rentao; Zhou, Zhongkun; Ma, Yunhao; Du, Kangjia; Sun, Mengze; Zhang, Hao; Tu, Hongyuan; Jiang, Xinrong; Lu, Juan; Tu, Lixue; Niu, Yuqing; Chen, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer is second only to heart disease as a cause of death, despite improvements in its early diagnosis and precision medicine. Due to the limitations of commonly used anticancer methods such as surgery, radiotherapy and chemotherapy, biological therapy, especially probiotics such as lactic acid bacteria, has received widespread attention. Lactobacillus has been proven to inhibit the proliferation of a variety of cancer cells. In this work, the effects of the cell-free culture supernatant of serofluid dish (CCS1) and the cell-free culture supernatant of Lactiplantibacillus plantarum YT013 (CCS2) isolated from serofluid dish on AGS, HCT116, HepG2 and PANC-1 cells were investigated. Based on the CCK-8 assay, CCS1 and CCS2 were shown to suppress the growth of cancer cells in a concentration-dependent manner. The IC50 values of CCS2 of AGS, HCT116, HepG2 and PANC-1 cells were 346.51  35.28, 1207.69  333.18, 650.94  123.78 and 808.96  126.27 μg/mL, respectively. In addition, the results of fluorescence microscopy showed that CCS2 changed cell morphology and treated with CCS2 (200, 400 and 800 μg/mL) for 48 h, AGS cell apoptosis was quantitatively surveyed by flow cytometry, showing 25.0%, 34.1%, and 42.6% total apoptotic cells. Moreover, western blotting confirmed that BAX, BAD and Caspase-3/8/9 were significantly upregulated and that BCL-2 was significantly downregulated in AGS cells treated with CCS2. These results indicated that CCS2 might lead to apoptosis via the endogenous mitochondrial apoptotic pathway. In summary, Lactiplantibacillus plantarum YT013 may be considered a good candidate for anticancer therapies.